A nano-titanium dioxide network composite mesoporous carbon-coated lithium manganese iron phosphate and a preparation method thereof

CN116706003BActive Publication Date: 2026-10-23WANHUA CHEM (SICHUAN) CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210171377.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-02-24
Publication Date
2026-10-23
Estimated Expiration
2042-02-24

AI Technical Summary

Technical Problem

[0004]本发明的目的在于解决水热制备磷酸锰铁锂导电性低、高倍率充放电性能差、循环寿命短的问题,提供一种纳米二氧化钛网络复合介孔碳包覆磷酸锰铁锂的制备方法

Benefits of technology

[0028]与现有技术相比,本发明的积极效果在于:

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a preparation method of nano titania network composite mesoporous carbon coated lithium manganese iron phosphate, and belongs to the field of lithium ion battery cathode materials. The main content of the application is that titania nanowires, water-soluble gelling agent and dispersant are dispersed in an aqueous solution as raw materials, and after being uniformly dispersed through ultrasonic dispersion, lithium manganese iron phosphate prepared through hydrothermal reaction is added into the solution, and after being ultrasonically dispersed, the solution is heated to generate a gel under stirring, and after the solution is cooled, the gel is converted into a solid gel. The gel mixture is transferred into a freeze dryer for vacuum freeze drying, and finally, nano titania network composite mesoporous carbon coated lithium manganese iron phosphate is obtained through sintering in a nitrogen atmosphere. The nano titania network composite mesoporous carbon coated lithium manganese iron phosphate prepared by the application has the characteristics of small particle size, uniform particle size distribution, high conductivity, large specific surface area and many active sites.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nanomaterial preparation, specifically relating to a method for preparing lithium manganese iron phosphate coated with nano-titanium dioxide network composite mesoporous carbon. Background Technology

[0002] Lithium-ion batteries, with their excellent electrochemical performance and high energy density, have been widely used in portable electronics, electric vehicles, and energy storage. However, manufacturing low-cost, high-energy-density, and long-cycle-life lithium-ion batteries remains a major challenge. The cathode material is a key component of lithium-ion batteries. Currently available ternary cathode materials include lithium cobalt oxide, lithium manganese oxide, nickel-cobalt-manganese ternary materials, and lithium iron phosphate. Among these, lithium iron phosphate has become the fastest-growing cathode material due to its long cycle life, high stability, excellent safety, abundant raw material sources, relatively low price, and environmental friendliness. It has been widely used in electric vehicles, power tools, large-scale energy storage systems, and many other fields.

[0003] However, lithium iron phosphate (LFP) has a low voltage platform, resulting in low energy density, making it difficult to meet the ever-increasing demand for high capacity and long battery life. Lithium manganese iron phosphate (LFP), while maintaining the stable olivine structure of LFP, improves the voltage platform and increases energy density. Currently, common methods for synthesizing LFP include solid-state methods, sol-gel methods, liquid-phase precipitation methods, hydrothermal methods, and microwave methods. Among these, the hydrothermal method is an important in-situ synthesis method for LFP, allowing precise control of particle size. It offers advantages such as small particle size, uniform particle size distribution, high conductivity and glycemic ratio, and a simple synthesis process with relatively low energy consumption. However, LFP itself has extremely poor conductivity (<10 ohms). -13 The conductivity (S / cm) of lithium manganese iron phosphate (LMP) is low, resulting in poor cycle performance and high-rate charge / discharge performance. Therefore, it is generally necessary to improve the conductivity, cycle, and rate performance of LMP by reducing particle size, carbon coating, or composite materials. Hydrothermal synthesis of LMP typically involves carbon coating the prepared LMP using organic pyrolysis or chemical vapor deposition after the hydrothermal process. Titanium dioxide is an excellent battery material due to its large lithium intercalation capacity, environmental friendliness, high stability, and long cycle life. Therefore, it is widely used in positive and negative electrode materials such as lithium iron phosphate, lithium manganese oxide, and lithium cobalt oxide. Titanium dioxide composite LMP materials are also a promising research direction. However, current titanium dioxide composite LMP materials still suffer from low conductivity, poor high-rate charge / discharge performance, and short cycle life. Summary of the Invention

[0004] The purpose of this invention is to solve the problems of low conductivity, poor high-rate charge-discharge performance, and short cycle life of lithium manganese iron phosphate prepared by hydrothermal methods, and to provide a method for preparing lithium manganese iron phosphate coated with nano-titanium dioxide network composite mesoporous carbon.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0006] A method for preparing lithium manganese iron phosphate coated with nano-titanium dioxide network composite mesoporous carbon, the steps of which are as follows:

[0007] (1) Add titanium dioxide nanowires, water-soluble gelling agent and dispersant to deionized water and ultrasonically disperse until the titanium dioxide nanowires are uniformly dispersed in the solution and the gelling agent and dispersant are completely dissolved to obtain a mixed dispersion.

[0008] (2) Add the hydrothermally prepared lithium manganese iron phosphate powder to the mixed dispersion in step (1), disperse it by ultrasonication, and then heat the solution under stirring until a gel is produced.

[0009] (3) After the gel is cooled to room temperature, it transforms into a solid gel and is transferred to a freeze dryer for freeze drying to obtain a titanium dioxide nanowire composite mesoporous carbon-coated lithium manganese iron phosphate precursor.

[0010] (4) The precursor obtained after freeze-drying was sintered at high temperature under a nitrogen atmosphere to obtain nano-titanium dioxide network composite mesoporous carbon-coated lithium manganese iron phosphate.

[0011] Preferably, in step (1) of the present invention, the titanium dioxide nanowires are analytical grade titanium dioxide nanowires with a diameter of 5-15 nm, a length of 10-50 μm, and a purity greater than 99.5%.

[0012] Preferably, in step (1) of the present invention, the concentration of the titanium dioxide nanowire dispersion is 0.02-0.1 mol / L, and more preferably 0.02-0.06 mol / L.

[0013] Preferably, in step (1) of the present invention, the water-soluble gelling agent is one or more of gellan gum, modified starch, agar, carrageenan, pectin, alginate, methylcellulose and hydroxypropyl methylcellulose, and the concentration of the gelling agent is 1-10 wt%, preferably 2-8 wt%.

[0014] Preferably, in step (1) of the present invention, the dispersant is one or more of polyethylene glycol 200, polyethylene glycol 400, polyvinyl alcohol and hexenyl bis-stearamide, and the concentration of the dispersant is 0.02-0.5 wt%, preferably 0.1-0.3 wt%.

[0015] Preferably, in step (1) of the present invention, the ultrasonic dispersion time is 30-120 min, more preferably 40-90 min;

[0016] Preferably, in step (2) of the present invention, the particle size of the lithium manganese iron phosphate is 100-400nm, preferably 200-300nm; the amount of lithium manganese iron phosphate added per liter of mixed dispersion is 1.5-5mol, preferably 2-3mol; the stirring speed is 100-300rpm, preferably 200-250rpm; and the heating temperature is 120-200℃, preferably 150℃-160℃.

[0017] Preferably, in step (3) of the present invention, the freeze-drying temperature is -80°C to -50°C, preferably -70°C to -60°C, the vacuum degree is 5-50Pa, preferably 5-20Pa; and the freeze-drying time is 10-30h, preferably 15-24h.

[0018] Preferably, the sintering apparatus is one of a nitrogen atmosphere tube furnace or a nitrogen atmosphere box furnace;

[0019] In step (4) of this invention, the nitrogen gas used is high-purity nitrogen gas with a flow rate of 200-800 ml / min. The preferred sintering process is as follows: heating to 200-250°C at a heating rate of 3-5°C / min and holding for 1-3 hours; heating to 400-450°C at a heating rate of 3-5°C / min and holding for 1-3 hours; heating to 750-820°C at a heating rate of 3-5°C / min and holding for 5-12 hours.

[0020] In this invention, steps (1) and (2) involve heating and cooling a solution containing titanium dioxide nanowires, a water-soluble gelling agent, a dispersant, and lithium manganese iron phosphate to form a gel, thereby uniformly dispersing the titanium dioxide nanowires in the system to form a nano-titanium dioxide coated network.

[0021] In this invention, steps (3) and (4) involve freeze-drying to induce self-shrinkage of the gel, reducing the spacing between lithium manganese iron phosphate particles. During sintering, the titanium dioxide nanowire network is fixed within the carbon coating layer. Simultaneously, this network formed between the lithium manganese iron phosphate particles hinders the growth of lithium manganese iron phosphate grains, resulting in lithium manganese iron phosphate with small grains and uniform particle size distribution.

[0022] This invention obtains coated carbon with a mesoporous structure through sol-gel, freeze-drying and nitrogen atmosphere sintering.

[0023] In this invention, the above method can be used to obtain nano-titanium dioxide network composite mesoporous carbon-coated lithium manganese iron phosphate with high conductivity and ion transport rate, small particle size, uniform particle size, long cycle life, and easily controllable carbon content.

[0024] The mechanism of this invention, which uses a nano-titanium dioxide network composite mesoporous carbon to coat lithium manganese iron phosphate, is as follows:

[0025] (1) Nanoscale titanium dioxide network coating of lithium manganese iron phosphate improves the electrochemical performance of the material: Titanium dioxide nanowires form a nanoscale titanium dioxide coating network in the gel, which is then solidified in the coated carbon layer after freeze-drying and high-temperature carbonization. These titanium dioxide networks fixed in the coated mesoporous carbon can effectively reduce the film impedance and charge transfer impedance of lithium manganese iron phosphate, and hinder the further growth of lithium manganese iron phosphate grains during the sintering process. The prepared lithium manganese iron phosphate material has a small particle size and uniform distribution, which helps to improve the electrochemical performance.

[0026] (2) The solvent water is sublimated by freeze drying to form a mesoporous structure in its original position, and then sintered in a high-temperature nitrogen atmosphere to obtain a carbon coating layer with a large specific surface area. The carbon content of the carbon-coated lithium manganese iron phosphate is controlled by controlling the concentration of water-soluble gelling agent in the solution and the sintering regime.

[0027] (3) Hydrothermal-synthesized lithium manganese iron phosphate is used directly as raw material. A carbon layer is coated on the surface of lithium manganese iron phosphate by liquid phase gel coating and recarbonization. This avoids the influence of repeated grinding and heating processes on crystal size and morphology in the traditional solid phase method. The carbon-coated lithium manganese iron phosphate prepared has a uniform particle size distribution and the carbon coating layer is uniform and controllable.

[0028] Compared with the prior art, the positive effects of the present invention are as follows:

[0029] 1. This invention obtains lithium manganese iron phosphate coated with nano-titanium dioxide network composite mesoporous carbon through a process of gel solidification, freeze drying and high temperature carbonization. The nano-titanium dioxide network coating can effectively reduce the film impedance and charge transfer impedance of lithium manganese iron phosphate, increase the conductivity and ionic conductivity of lithium manganese iron phosphate, and improve the electrochemical performance and low temperature performance of the material.

[0030] 2. The carbon source used in this invention is different from sucrose, glucose, etc., which are commonly used in carbon coating in the industry. It directly uses water-soluble gelling agent for high-temperature carbonization as the coating carbon layer, without the need to add other carbon sources, thus expanding the range of carbon source selection. Moreover, the carbon coating layer is uniform, easy to adjust, and has high consistency.

[0031] 3. The carbon-coated mesoporous structure prepared by the present invention is obtained by in-situ sublimation of water in the gel skeleton during freeze-drying. The mesopores are uniform in size and evenly distributed. These mesoporous structures can effectively increase the specific surface area and the number of active sites of lithium manganese iron phosphate composite material.

[0032] 4. This invention forms a nano-titanium dioxide network between lithium manganese iron phosphate materials through gel solidification and freeze-drying, which hinders the grain growth of lithium manganese iron phosphate materials during sintering, resulting in lithium manganese iron phosphate materials with uniform particle size distribution, shortening the ion transport path, and improving the rate performance of the material.

[0033] 5. This invention can obtain carbon-coated lithium manganese iron phosphate with different carbon contents by precisely controlling the raw materials and sintering process;

[0034] 6. The carbon-coated manganese iron phosphate particles prepared by this invention have small particle size and uniform particle size distribution, eliminating the need for high-temperature solid-phase sand milling and spray drying processes, effectively reducing energy consumption in the production process, saving production costs, and reducing waste gas emissions, making it an environmentally friendly production process. Specific implementation methods

[0035] The technical solution of the present invention will be further described below with reference to specific embodiments. The embodiments provide specific implementation methods and specific operation processes, but the protection scope of the present invention is not limited to the following embodiments.

[0036] The raw materials for the examples and comparative examples are as follows:

[0037] Raw material table for examples and comparative examples

[0038] Lithium manganese iron phosphate - self made Titanium dioxide nanowires ≥99.5% Shanghai Jianghu Titanium Dioxide Co., Ltd. Gel food grade Sinopharm Chemical Reagent Co., Ltd. Cold weather powder food grade Sinopharm Chemical Reagent Co., Ltd. pectin ≥74.0% Aladdin Biochemical Technology Co., Ltd. glucose food grade Aladdin Biochemical Technology Co., Ltd. Methylcellulose food grade Sinopharm Chemical Reagent Co., Ltd. PEG200 Analytical Pure Sinopharm Chemical Reagent Co., Ltd. PEG400 Analytical Pure Sinopharm Chemical Reagent Co., Ltd. Polyvinyl alcohol Analytical Pure Sinopharm Chemical Reagent Co., Ltd.

[0039] Preparation of lithium manganese iron phosphate

[0040] Ferrous sulfate heptahydrate, manganese sulfate, phosphoric acid, and lithium hydroxide were added to a beaker in a molar ratio of 0.4:0.6:1:3. Water was added until the solution was completely dissolved. The solution was then transferred to a hydrothermal reactor and heated to 180°C for 5 hours. The resulting precipitate was filtered, washed, and dried to obtain a self-made lithium manganese iron phosphate sample with a particle size of approximately 200-300 nm.

[0041] Test characterization methods

[0042] The specific surface area and pore size distribution of the samples were determined using a specific surface area and pore size analyzer (BET analyzer).

[0043] The sample material was mixed with binder (PTFE) and conductive carbon black in a ratio of 9:0.5:0.5 and ground evenly in an agate mortar to obtain a slurry. The slurry was then evenly coated onto aluminum foil, vacuum dried, and cut into sheets to obtain the positive electrode. Using lithium foil as the negative electrode, Celgard 2400 as the separator, and 1 mol / L LiPF6 / EC+DEC as the electrolyte, CR2032 button cells were assembled in a glove box for electrochemical performance testing, with a test voltage range of 2.0-3.75V.

[0044] Example 1

[0045] (1) Precursor preparation: 0.2g titanium dioxide nanowires, 1.2g gellan gum and 70mg PEG200 were added to 30ml of water and sonicated for 30min until the titanium dioxide nanowires were evenly dispersed and the gellan gum and PEG200 were completely dissolved.

[0046] (2) Obtaining solid gel: 10g of hydrothermally synthesized lithium manganese iron phosphate was added to the mixed solution obtained in step (1) at a stirring speed of 300rpm and ultrasonically dispersed for 1 hour. Then, the mixed solution was heated to 180°C at a stirring speed of 250rpm until the solution began to form a gel. Heating was stopped and the solution was allowed to cool naturally to room temperature in the air.

[0047] (3) Freeze-drying: The cooled gel was transferred to a freeze dryer for vacuum freeze-drying. The cold trap temperature was -65℃, the vacuum degree was 15Pa, and the drying time was 24 hours.

[0048] (4) Nitrogen atmosphere sintering: The freeze-dried sample was transferred to a tube furnace, and the nitrogen flow rate was adjusted to 600 ml / min. After nitrogen atmosphere replacement, nitrogen atmosphere sintering was performed. The temperature was increased to 200℃ at a rate of 5℃ / min and held for 2 h, then increased to 400℃ at a rate of 4℃ / min and held for 2 h, and finally increased to 790℃ at a rate of 3℃ / min and held for 8 h. After cooling, lithium manganese iron phosphate sample coated with nano-titanium dioxide network composite mesoporous carbon was obtained.

[0049] The lithium manganese iron phosphate material prepared by the above method has a network coating structure of nano-titanium dioxide composite mesoporous carbon, with a specific surface area of ​​16.67 m². 2 The prepared lithium manganese iron phosphate composite material exhibits a mesoporous structure with an average pore size of 3 nm and a first discharge capacity of 158 mAh / g at a 0.1C rate and a discharge capacity of 132 mAh / g at a 1C rate.

[0050] Example 2:

[0051] (1) Precursor preparation: Add 0.15g of titanium dioxide nanowires, 1.5g of agar powder and 50mg of PEG400 to 30ml of water, and sonicate for 60min until the titanium dioxide nanowires are evenly dispersed and the agar powder and PEG400 are completely dissolved.

[0052] (2) Obtaining solid gel: 12g of hydrothermally synthesized lithium manganese iron phosphate was added to a mixed solution of agar and PEG400 under stirring and ultrasonically dispersed for 1 hour. Then, the mixed solution was heated to 160°C under stirring at 200 rpm until the solution began to form a gel. Heating was stopped and the solution was allowed to cool naturally to room temperature in the air.

[0053] (3) Freeze-drying: The cooled gel was transferred to a freeze dryer for vacuum freeze-drying. The cold trap temperature was -70℃, the vacuum degree was 20Pa, and the drying time was 10 hours.

[0054] (4) Nitrogen atmosphere sintering: The freeze-dried sample was transferred to a tube furnace, and the nitrogen flow rate was adjusted to 500 ml / min. After nitrogen atmosphere replacement, nitrogen atmosphere sintering was performed. The temperature was increased to 220℃ at a rate of 4℃ / min and held for 1 h, then increased to 450℃ at a rate of 3℃ / min and held for 1 h, and finally increased to 780℃ at a rate of 4℃ / min and held for 10 h. After cooling, lithium manganese iron phosphate sample coated with nano-titanium dioxide network composite mesoporous carbon was obtained.

[0055] The lithium manganese iron phosphate material prepared by the above method has a network coating structure of nano-titanium dioxide composite mesoporous carbon, with a specific surface area of ​​15.82 m². 2 The prepared lithium manganese iron phosphate composite material exhibits a mesoporous structure with an average pore size of 4 nm and a density of 1 g / g. The initial discharge capacity at 0.1C is 161 mAh / g, and the discharge capacity at 1C is 135 mAh / g.

[0056] Example 3:

[0057] (1) Precursor preparation: 0.12g of titanium dioxide nanowires, 1g of pectin and 60mg of polyvinyl alcohol were added to 30ml of water and sonicated for 50min until the titanium dioxide nanowires were evenly dispersed and the pectin and polyvinyl alcohol were completely dissolved.

[0058] (2) Obtaining solid gel: 8g of hydrothermally synthesized lithium manganese iron phosphate was added to a mixed solution of agar and dicyandiamide under stirring and ultrasonically dispersed for 1 hour. Then, the mixed solution was heated to 150°C under stirring at 150 rpm until the solution began to form a gel. Heating was stopped and the solution was allowed to cool naturally to room temperature in the air.

[0059] (3) Freeze-drying: The cooled gel was transferred to a freeze dryer for vacuum freeze-drying. The cold trap temperature was -60℃, the vacuum degree was 30Pa, and the drying time was 20 hours.

[0060] (4) Nitrogen atmosphere sintering: The freeze-dried sample was transferred to a tube furnace, and the nitrogen flow rate was adjusted to 400 ml / min. After nitrogen atmosphere replacement, nitrogen atmosphere sintering was performed. The temperature was increased to 250℃ at a rate of 3℃ / min and held for 1.5 h. Then, the temperature was increased to 400℃ at a rate of 3℃ / min and held for 1.5 h. Finally, the temperature was increased to 760℃ at a rate of 3℃ / min and held for 12 h. After cooling, lithium manganese iron phosphate sample coated with nano-titanium dioxide network composite mesoporous carbon was obtained.

[0061] The lithium manganese iron phosphate material prepared by the above method has a network coating structure of nano-titanium dioxide composite mesoporous carbon, with a specific surface area of ​​18.25 m². 2 The prepared lithium manganese iron phosphate composite material exhibits a mesoporous structure with an average pore size of 4 nm and a first discharge capacity of 159 mAh / g at a 0.1C rate and a discharge capacity of 133 mAh / g at a 1C rate.

[0062] Example 4:

[0063] (1) Precursor preparation: Add 0.048g of titanium dioxide nanowires, 0.3g of agar powder and 150mg of PEG400 to 30ml of water and sonicate for 90min until the titanium dioxide nanowires are evenly dispersed and the pectin and PEG400 are completely dissolved.

[0064] (2) Obtaining solid gel: 16g of hydrothermally synthesized lithium manganese iron phosphate was added to a mixed solution of agar and dicyandiamide under stirring and ultrasonically dispersed for 1 hour. Then, the mixed solution was heated to 200°C under stirring at 100 rpm until the solution began to form a gel. Heating was stopped and the solution was allowed to cool naturally to room temperature in the air.

[0065] (3) Freeze-drying: The cooled gel was transferred to a freeze dryer for vacuum freeze-drying. The cold trap temperature was -80℃, the vacuum degree was 5Pa, and the drying time was 30 hours.

[0066] (4) Nitrogen atmosphere sintering: The freeze-dried sample was transferred to a tube furnace, and the nitrogen flow rate was adjusted to 200 ml / min. After nitrogen atmosphere replacement, nitrogen atmosphere sintering was performed. The temperature was increased to 250℃ at a rate of 3℃ / min and held for 3 h. The temperature was then increased to 420℃ at a rate of 5℃ / min and held for 3 h. Finally, the temperature was increased to 820℃ at a rate of 5℃ / min and held for 5 h. After cooling, lithium manganese iron phosphate sample coated with nano-titanium dioxide network composite mesoporous carbon was obtained.

[0067] The lithium manganese iron phosphate material prepared by the above method has a network coating structure of nano-titanium dioxide composite mesoporous carbon, with a specific surface area of ​​14.76 m². 2 The prepared lithium manganese iron phosphate composite material exhibits a mesoporous structure with an average pore size of 4 nm and a first discharge capacity of 158 mAh / g at a 0.1C rate and a discharge capacity of 128 mAh / g at a 1C rate.

[0068] Example 5:

[0069] (1) Precursor preparation: 0.24g of titanium dioxide nanowires, 3g of gellan gum and 6mg of PEG200 were added to 30ml of water and sonicated for 120min until the titanium dioxide nanowires were evenly dispersed and the pectin and PEG200 were completely dissolved.

[0070] (2) Obtaining solid gel: 26.7g of hydrothermally synthesized lithium manganese iron phosphate was added to a mixed solution of agar and dicyandiamide under stirring and ultrasonically dispersed for 1 hour. Then, the mixed solution was heated to 120°C under stirring at 200 rpm until the solution began to form a gel. Heating was stopped and the solution was allowed to cool naturally to room temperature in the air.

[0071] (3) Freeze-drying: The cooled gel was transferred to a freeze dryer for vacuum freeze-drying. The cold trap temperature was -50℃, the vacuum degree was 50Pa, and the drying time was 20 hours.

[0072] (4) Nitrogen atmosphere sintering: The freeze-dried sample was transferred to a tube furnace, and the nitrogen flow rate was adjusted to 800 ml / min. After nitrogen atmosphere replacement, nitrogen atmosphere sintering was performed. The temperature was increased to 220℃ at a rate of 3℃ / min and held for 2 h. The temperature was then increased to 420℃ at a rate of 5℃ / min and held for 2.5 h. Finally, the temperature was increased to 750℃ at a rate of 4℃ / min and held for 8 h. After cooling, lithium manganese iron phosphate sample coated with nano-titanium dioxide network composite mesoporous carbon was obtained.

[0073] The lithium manganese iron phosphate material prepared by the above method has a network coating structure of nano-titanium dioxide composite mesoporous carbon, with a specific surface area of ​​18.25 m². 2 The prepared lithium manganese iron phosphate composite material exhibits a mesoporous structure with an average pore size of 4 nm and a first discharge capacity of 159 mAh / g at a 0.1C rate and a discharge capacity of 139 mAh / g at a 1C rate.

[0074] Comparative Example 1

[0075] (1) Preparation of precursor: Add 1.5g of agar powder and 50mg of PEG400 to 30ml of water and sonicate for 60min until completely dissolved.

[0076] (2) Obtaining solid gel: 12g of hydrothermally synthesized lithium manganese iron phosphate was added to a mixed solution of agar and PEG400 under stirring and ultrasonically dispersed for 1 hour. Then, the mixed solution was heated to 160°C under stirring at 200 rpm until the solution began to form a gel. Heating was stopped and the solution was allowed to cool naturally to room temperature in the air.

[0077] (3) Freeze-drying: The cooled gel was transferred to a freeze dryer for vacuum freeze-drying. The cold trap temperature was -70℃, the vacuum degree was 20Pa, and the drying time was 10 hours.

[0078] (4) Nitrogen atmosphere sintering: The freeze-dried sample was transferred to a tube furnace, and the nitrogen flow rate was adjusted to 500 ml / min. After nitrogen atmosphere replacement, nitrogen atmosphere sintering was performed. The temperature was increased to 220℃ at a rate of 4℃ / min and held for 1 h. The temperature was then increased to 450℃ at a rate of 3℃ / min and held for 1 h. Finally, the temperature was increased to 780℃ at a rate of 4℃ / min and held for 10 h. After cooling, mesoporous carbon-coated lithium manganese iron phosphate samples were obtained.

[0079] The lithium manganese iron phosphate material prepared by the above method has a network coating structure of nano-titanium dioxide composite mesoporous carbon, with a specific surface area of ​​10.62 m². 2 The prepared lithium manganese iron phosphate composite material exhibits a mesoporous structure with an average pore size of approximately 5 nm. The initial discharge capacity at 0.1C is 154 mAh / g, and the discharge capacity at 1C is 119 mAh / g.

[0080] Comparative Example 2

[0081] (1) Precursor preparation: 0.12g of nano silica, 1.5g of agar powder and 50mg of PEG400 were added to 30ml of water and sonicated for 60min until the titanium dioxide nanowires were evenly dispersed and the agar powder and PEG400 were completely dissolved.

[0082] (2) Obtaining solid gel: 12g of hydrothermally synthesized lithium manganese iron phosphate was added to a mixed solution of agar and PEG400 under stirring and ultrasonically dispersed for 1 hour. Then, the mixed solution was heated to 160°C under stirring at 200 rpm until the solution began to form a gel. Heating was stopped and the solution was allowed to cool naturally to room temperature in the air.

[0083] (3) Freeze-drying: The cooled gel was transferred to a freeze dryer for vacuum freeze-drying. The cold trap temperature was -70℃, the vacuum degree was 20Pa, and the drying time was 10 hours.

[0084] (4) Nitrogen atmosphere sintering: The freeze-dried sample was transferred to a tube furnace, and the nitrogen flow rate was adjusted to 500 ml / min. After nitrogen atmosphere replacement, nitrogen atmosphere sintering was performed. The temperature was increased to 220℃ at a rate of 4℃ / min and held for 1 h, then increased to 450℃ at a rate of 3℃ / min and held for 1 h, and finally increased to 780℃ at a rate of 4℃ / min and held for 10 h. After cooling, lithium manganese iron phosphate sample coated with nano-silica composite mesoporous carbon was obtained.

[0085] The lithium manganese iron phosphate material prepared by the above method has a network coating structure of nano-titanium dioxide composite mesoporous carbon, with a specific surface area of ​​11.32 m². 2The prepared lithium manganese iron phosphate composite material exhibits a mesoporous structure with an average pore size of 4 nm and a first discharge capacity of 136 mAh / g at a 0.1C rate and a discharge capacity of 107 mAh / g at a 1C rate.

[0086] Comparative Example 3

[0087] (1) Precursor preparation: Add 0.12g of titanium dioxide nanowires, 1g of glucose and 60mg of PEG400 to 30ml of water and sonicate for 50min until completely dissolved.

[0088] (2) Obtaining the precursor: 8g of hydrothermally synthesized lithium iron manganese phosphate was added to the mixed solution under stirring and ultrasonically dispersed for 1 hour. Then it was placed in an oven and dried at 90°C for 20 hours to obtain carbon-coated lithium iron manganese phosphate precursor.

[0089] (3) Nitrogen atmosphere sintering: The dried sample was transferred to a tube furnace, and the nitrogen flow rate was adjusted to 400 ml / min. After nitrogen atmosphere replacement, nitrogen atmosphere sintering was performed. The temperature was increased to 250℃ at a rate of 3℃ / min and held for 1.5 h. Then, the temperature was increased to 400℃ at a rate of 3℃ / min and held for 1.5 h. Finally, the temperature was increased to 760℃ at a rate of 3℃ / min and held for 12 h. After cooling, carbon-coated lithium manganese iron phosphate samples were obtained.

[0090] The lithium manganese iron phosphate material prepared by the above method has a network coating structure of nano-titanium dioxide composite mesoporous carbon, with a specific surface area of ​​14.68 m². 2 / g, without mesoporous structure. The prepared lithium manganese iron phosphate composite material has an initial discharge capacity of 153 mAh / g at 0.1C rate and a discharge capacity of 122 mAh / g at 1C rate.

[0091] Table 1. Performance Comparison of Lithium Manganese Iron Phosphate Composites Prepared by Different Methods

[0092] Example 1 16.67 3 158 132 Example 2 15.82 4 161 135 Example 3 18.25 4 159 133 Example 4 14.76 4 158 128 Example 5 18.65 4 159 139 Comparative Example 1 10.62 5 154 119 Comparative Example 2 11.32 4 136 107 Comparative Example 3 14.68 - 153 122

Claims

1. A method for preparing lithium manganese iron phosphate coated with a nano-titanium dioxide network composite mesoporous carbon, characterized in that... The steps include: (1) Add titanium dioxide nanowires, water-soluble gelling agent and dispersant to deionized water and ultrasonically disperse until the titanium dioxide nanowires are uniformly dispersed in the solution and the gelling agent and dispersant are completely dissolved to obtain a mixed dispersion. (2) Add the hydrothermally prepared lithium manganese iron phosphate powder to the mixed dispersion in step (1), disperse it by ultrasonication, and then heat the solution under stirring until a gel is produced; (3) After the gel is cooled to room temperature, it transforms into a solid gel and is transferred to a freeze dryer for freeze drying to obtain a titanium dioxide nanowire composite mesoporous carbon-coated lithium manganese iron phosphate precursor. (4) The precursor obtained after freeze-drying was sintered at high temperature under a nitrogen atmosphere to obtain nano-titanium dioxide network composite mesoporous carbon-coated lithium manganese iron phosphate.

2. The preparation method according to claim 1, characterized in that, In step (1), the titanium dioxide nanowires are analytical grade titanium dioxide nanowires with a diameter of 5-15 nm, a length of 10-50 μm, and a purity greater than 99.5%.

3. The preparation method according to claim 1, characterized in that, In step (1), the concentration of the titanium dioxide nanowire dispersion is 0.02-0.1 mol / L.

4. The preparation method according to any one of claims 1-3, characterized in that, In step (1), the water-soluble gelling agent is one or more of gellan gum, modified starch, agar, carrageenan, pectin, alginate, methylcellulose and hydroxypropyl methylcellulose, and the concentration of the gelling agent is 1-10 wt%.

5. The preparation method according to any one of claims 1-3, characterized in that, In step (1), the dispersant is one or more of polyethylene glycol 200, polyethylene glycol 400, polyvinyl alcohol and hexenyl bis-stearamide, and the concentration of the dispersant is 0.02-0.5 wt%.

6. The preparation method according to any one of claims 1-3, characterized in that, In step (2), the particle size of the lithium manganese iron phosphate is 100-400 nm; the amount of lithium manganese iron phosphate added per liter of mixed dispersion is 1.5-5 mol, the stirring speed is 100-300 rpm, and the heating temperature is 120-200℃.

7. The preparation method according to any one of claims 1-3, characterized in that, In step (3), the freeze-drying temperature is -80℃ to -50℃, the vacuum degree is 5-50Pa, and the freeze-drying time is 10-30h.

8. The preparation method according to any one of claims 1-3, characterized in that, In step (4), the sintering device is one of a nitrogen atmosphere tube furnace or a nitrogen atmosphere box furnace.

9. The preparation method according to any one of claims 1-3, characterized in that, In step (4), the nitrogen gas used is high-purity nitrogen gas with a flow rate of 200-800 ml / min. The sintering process is as follows: heat up to 200-250℃ at a heating rate of 3-5℃ / min and hold for 1-3 hours; heat up to 400-450℃ at a heating rate of 3-5℃ / min and hold for 1-3 hours; heat up to 750-820℃ at a heating rate of 3-5℃ / min and hold for 5-12 hours.

10. A nano-titanium dioxide network composite mesoporous carbon-coated lithium manganese iron phosphate, which is obtained by the preparation method described in any one of claims 1-9.

Citation Information

Patent Citations

  • Method for performing carbon coating modification on nano-powder by adopting water-soluble polymer

    CN103035899A

  • Method for modifying positive electrode of lithium ion battery by adding metal oxide / carbon composite material

    CN105390700A